2012
DOI: 10.1186/gb-2012-13-10-r91
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic transgenerational inheritance of somatic transcriptomes and epigenetic control regions

Abstract: BackgroundEnvironmentally induced epigenetic transgenerational inheritance of adult onset disease involves a variety of phenotypic changes, suggesting a general alteration in genome activity.ResultsInvestigation of different tissue transcriptomes in male and female F3 generation vinclozolin versus control lineage rats demonstrated all tissues examined had transgenerational transcriptomes. The microarrays from 11 different tissues were compared with a gene bionetwork analysis. Although each tissue transgenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
162
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(167 citation statements)
references
References 57 publications
5
162
0
Order By: Relevance
“…Epigenetic polymorphism has attracted enormous interest in recent years. Several recent studies investigating the connection between genetic variation and epigenetic variation revealed that epigenetic polymorphisms are likely the result of a complex interplay between genetic and environmental factors (Anway et al 2005;Li et al 2011;Crews et al 2012;Skinner et al 2012). Our finding provides additional support for the potential functional impact of epigenetic polymorphisms.…”
Section: Genome Research 1533supporting
confidence: 75%
See 1 more Smart Citation
“…Epigenetic polymorphism has attracted enormous interest in recent years. Several recent studies investigating the connection between genetic variation and epigenetic variation revealed that epigenetic polymorphisms are likely the result of a complex interplay between genetic and environmental factors (Anway et al 2005;Li et al 2011;Crews et al 2012;Skinner et al 2012). Our finding provides additional support for the potential functional impact of epigenetic polymorphisms.…”
Section: Genome Research 1533supporting
confidence: 75%
“…Unlike genetic polymorphisms such as SNPs and copy number variation, epigenetic polymorphisms can be influenced by both genetic and environmental determinants (Anway et al 2005;Li et al 2011;Crews et al 2012;Skinner et al 2012). In our study, we obtained biological replicates from two individuals for the breast, fetal brain, and blood data sets.…”
Section: Dmrs Between Individuals Overlap With Gene Regulatory Elementsmentioning
confidence: 99%
“…These RNA samples were then subjected to labeling, hybridization, washing, data acquisition and analyses as described previously. 57 Bioinformatic analysis. For piRNA-mRNA mapping, coding sequences (CDS), 3 0 UTRs, and 5 0 UTRs for all up or downregulated mRNAs with Po0.05 and fold change 41.2 (a total of 2161 genes) and 3290 randomly chosen mRNAs determined to be unregulated by MIWI2 in our microarray analyses were collected from ENSEMBL database (release 71).…”
Section: Discussionmentioning
confidence: 99%
“…The inherited changes were monitored in the third generation after treatment (1315). Effects on DNA methylation reprogramming were suggested as a major mechanism for transgenerational inheritance of chromatin modifications.…”
Section: Introductionmentioning
confidence: 99%